Penentuan Dosis Pupuk Berdasarkan Data Tonase Tandan Buah Segar (TBS) pada Perkebunan Kelapa Sawit - Winaldo Tjandra; Candra Ginting; Sri Gunawan (Program Studi Agroteknologi INSTIPER, 2023)
The productivity of Fresh Fruit Bunch (FFB) in Indonesia is relatively low with an average productivity of below 15 tonnes.ha-1.year-1,which is still very far below its potential, which is around 25 tonnes.ha-1. year-1, one of the contributing factors is the application of fertilizers. neither the type nor the dose has been done precisely. Research on Determining Fertilizer Dosage Based on FFB Â tonnage data for oil palm plantations has been carried out from March to October 2022 at a private oil palm plantation company located in Nunukan Regency, North Kalimantan Province. The research was carried out on an area of â€‹â€‹812 ha which was divided into 28 blocks, consisting of 7 treatments each carried out in 4 blocks as repetition. The soil pH conditions are relatively neutral, namely between 6.0-6.9. Fertilizers used are also of various kinds, namely Urea, Rock phosphate, Muriate of potash, Kieserit and Dolomite. The dosage of fertilizer is determined based on the tonnage of fresh fruit bunches produced and compared with the dose of fertilizer according to the recommendations from the leaf sampling unit. This study uses monthly data for each block from March to October 2022 which includes: average stem weight (BJR), number of stems per tree (JJG/PKK), and productivity (tons.ha-1.month-1). The data obtained were then analyzed for variance and continued with Duncan's multiple range test. The results showed that in March, April and October there was a significant difference between the treatments where in March there was a difference in the productivity of fresh fruit bunches where the application of Urea-Rph-MOP-Kieserite fertilizer was 4.3-2.5-1 respectively. .9-2.9 respectively in kg.principle-1.year-1 (P1) shows the highest productivity. In April and October there was a significant difference in the yield per tree where in April the Urea-Rph-MOP fertilizer application treatment was 2.4-1.6-1.8 respectively in kg.principal-1 year-1 (P5) showed that the number of shoots per tree tended to be higher than the other treatments, whereas in October the number of stems per tree tended to be higher in treatment P1. However, there was no significant difference in average length weight from March to October. Thus the dosage of fertilizer can be determined based on fresh fruit bunch tonnage data as an option other than based on the results of leaf sampling units to be implemented in the field.